PENERAPAN SLOW STROKE BACK MASSAGE THERAPY PADA LANSIA DI RSUD EMBUNG FATIMAH KOTA BATAM - Jessica Jessica; Yulia Devi Putri (Ensiklopedia Research and Community Service Review, 2026)
Non-hemorrhagic stroke is a cerebral blood flow disorder caused by arterial obstruction, resulting in tissue damage. Data from the Batam City Health Office recorded 572 cases, ranking 19th overall. This paper aims to provide medical-surgical nursing care through the application of slow stroke back massage therapy at Embung Fatimah General Hospital, Batam. The method employed is a case study based on nursing care stages, including assessment, data analysis, diagnosis, intervention, implementation, and evaluation. Results demonstrated a reduction in pain, with the pain scale decreasing from 7 on the first day to 2 on the third day, consistent with the objectives and outcome criteria. The application of slow stroke back massage proved effective as a non-pharmacological therapy to reduce pain in non-hemorrhagic stroke patients, suggesting its potential as an appropriate nursing intervention.Keywords: Elderly; Non-Hemorrhagic; Slow Stroke Back Massage Theraphy